Aspergillus Species and Antifungals Susceptibility in Clinical Setting in the North of Portugal: Cryptic Species and Emerging Azoles Resistance in A. fumigatus - Pinto, Eugénia; Monteiro, Carolina; Maia, Marta; Faria, Miguel A.; Lopes, Virgínia; Lameiras, Catarina; Pinheiro, Dolores (Frontiers in Microbiology, 2018)
Aspergillus spp. are agents of a broad-spectrum of diseases among humans. Their growing resistance to azoles, the cornerstone in the management of human aspergillosis, is a worrisome problem around the world. Considering lack of data from Portugal on this topic, particularly from the northern region, a retrospective surveillance study was planned to assess frequency of cryptic Aspergillus species and azoles resistance. A total of 227 clinical isolates, mainly from the respiratory tract (92.1%), collected from three hospitals serving a population of about three million people, were studied for their epidemiology and antifungal susceptibility patterns determined by the E.DEF.9.3 protocol of EUCAST. Employing molecular methods, seven Aspergillus complexes were identified; Aspergillus fumigatus sensu stricto was the most frequent isolate (86.7%). A 7.5% prevalence of cryptic species was found; A. welwitschiae (A. niger complex-3.1%) and A. lentulus (A. fumigatus complex-2.2%) were the most frequent. Amongst cryptic species, it was found a percentage of resistance to voriconazole, posaconazole and isavuconazole of 47.1, 82.4 and 100%, respectively. Five A. fumigatus sensu stricto showed pan-azole resistance. Sequencing their cyp51A gene revealed the presence of one isolate with TR46/Y121F/T289A mutation and two isolates with TR34/L98H mutation. This study emphasizes the need to identify strains to the species level and to evaluate their antifungal susceptibility in all human originated Aspergillus spp. isolates, particularly those from invasive aspergillosis.